MEMBACA MAKNA REGALIA SEBAGAI INSPIRASI UNTUK PENDIDIKAN BERKUALITAS YANG MERATA - Septarina, Sri Wahyuning; Sentavito, Eko Wahyu; Siswono, Tommi; Jovita, Gisela (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2024)
Sri Sultan Hamengku Buwono’s leadership character as a king cannot be separated from several heirlooms called regalia. According to the regalia philosophy, each heirloom represents eight character symbols that can be role models. The character values of the nation's children are very important because they are in line with and have an influence on educational progress. This article discusses the meaning of the regalia philosophy in the form of character values of the nation's children in accordance with the ideals of a Golden Indonesia 2045 by optimizing the role of the younger generation through leadership and influence at the global level. The research methodology used is descriptive qualitative using literature data techniques, interviews and observation. This article aims to inspire the nation's children to become a golden generation who have leadership character values with equitable and quality education. The author hopes that this paper will have a positive impact after knowing the meaning of the symbols of the regalia.